The Prediction of Third Party Funds, Interest Rates, and Non-Performing Loans toward Loan To Deposit Ratios and Its Impact on Return on Assets on Commercial Banks in Indonesia - Ni Nyoman Sawitri (Jurnal Manajemen, 2018)
This research aims to analyze the influence of third party funds, Bank Indonesia Certificates, and non-performing loans on return on assets and loan deposit ratio and the effect of loan deposit ratio on return on assets of commercial banks in Indonesia. The sample of this research is commercial bank listed Bursa Efek Indonesia period 2011 - 2015. There are 15 banks that meet the criteria as research samples with assets above IDR 50 Trillion. Hypothesis testing uses path analysis techniques. The results of this research indicate that TPF, BIC and NPL are partially and simultaneously influential and significant to the LDR, while TPF, BIC, NPL simultaneously also have an effect and significant effect on ROA, and LDR affects ROA but is not significant.